Determination of smoldering time and thermal characteristics of firebrands under laboratory conditions. (July 2017) - Fateev, Vladimir; Agafontsev, Mikhail; Volkov, Sergey; Filkov, Alexander
Abstract: The laboratory experiment was conducted to simulate the transfer of smouldering particles produced in forest wildfires by a heated gas flow. The pine bark pieces with the linear dimensions L =(15; 20; 30) mm and a thickness of h =(4−5) mm were selected as model particles. The rate and temperature of the incident flow varied in the range of 1–3 m/s and 80–85 °C, respectively. The temperature of the samples was recorded using a thermal imager. To determine the minimum smouldering temperature of pine bark, the thermal analysis was conducted. The minimum smouldering temperature of pine bark was found to be 190 °C. This temperature will cause thermal decomposition of bark only at the first stage (oxidation of resinous components). In the study the smouldering time, the temperature and the weight of samples were obtained and analyzed under various experimental conditions. The data analysis shows that the increase in the particle size leads to the decrease in their mass loss, and the rate change of the incident flow does not practically influence the mass change. For particles with the linear dimensions of 10 mm and 20 mm, the mass varies from 6% to 25%. The maximum mass loss is observed for the flows with a rate of 1 and 2 m/s. The results have shown that the increase in the particle size leads to the increase in the smouldering time. The position of the particle plays an important role, the effect of which increases with increasing the particle size. The calculations showed that the smouldering time of bark samples is long enough for the particles to serve as new sources of spot fires. The particles were found to be transported to a distance of 218 m from the fire line which can certainly influence the propagation of the fire front.